2020
DOI: 10.21203/rs.3.rs-17055/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends of multimorbidity in 15 European countries: a population-based study in community-dwelling adults aged 50 and over

Abstract: Background: The objective of this work was to analyse the prevalence trends of multimorbidity among European community-dwelling adults.Methods: A temporal series study based on waves 1, 2, 4, 5, 6 and 7 of the Survey of Health, Ageing and Retirement in Europe (SHARE) was conducted, and community-dwelling participants aged 50+ (n=274,614) from 15 European countries were selected for the period 2004-2017. Prevalence, adjusted by age, Average Annual Percentage Change (APC) and 95% confidence interval (95% CI) we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…A study in Canada found that the increase in multimorbidity prevalence could be attributed to obesity 20 . Another study conducted in European countries discussed that the improvement of diagnostic technology might also contribute to the increase of multimorbidity 21 . The increasing prevalence of multimorbidity observed between 2000 and 2014 could also be explained by the increasing burden of obesity-related chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Canada found that the increase in multimorbidity prevalence could be attributed to obesity 20 . Another study conducted in European countries discussed that the improvement of diagnostic technology might also contribute to the increase of multimorbidity 21 . The increasing prevalence of multimorbidity observed between 2000 and 2014 could also be explained by the increasing burden of obesity-related chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although government strategies varied substantially across countries the mitigation measures generally involved limiting human mobility (e.g., travel restrictions and quarantines), physical distancing measures (e.g., forbidding mass gatherings), closures (e.g., of schools, public spaces and businesses) and public health interventions (e.g., mandatory mask-wearing and population-scale testing) (Souza et al 2021, Cross et al 2020. Even though these restrictions were broadly effective in slowing viral transmission, they were also slowing down the economies of most countries (Decerf et al 2021, Bessell 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have increasingly explored the association of lifestyle and sociodemographic factors with multimorbidity, given the important relationship that they have and their impact on multimorbidity [7,[11][12][13][14]. In Portugal, however, there seem to be no studies on these associations.…”
Section: Introductionmentioning
confidence: 99%